PENGARUH BERAT MEDIA DAN JUMLAH BIBIT TERHADAP PERTUMBUHAN DAN PRODUKSI KENTANG (Solanum tuberosum L.) DI DALAM POLYBAG - Ulfah Ghina Fathiyyah; Munifatul Izzati; Sri Haryanti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Potatoes (Solanum tuberosum L) are one of the plants that become source of carbohydrates that help strengthening food. Potatoes are an annual crop that are not environmentally friendly because the potatoes can accelerate the rate of erosion. Therefore, a cultivation method is needed in polybag. Planting in polybag need to know the weight of media and seeds number for growth and production of potatoes running optimally. The purpose of this study is examine potato cultivation in polybag to improving potato growth and production. Parameters observed were plant height, wet weight of potato, tuber number, tuber weight and tuber weight/polybag. The treatments were given are media weight (V7: 7kg and V10: 10 kg) planting potatoes in land as a control and number of seeds (2 grains: 3grains and 4grains). The treatment in this research do with factorial completely randomized design in 9 different treatment and 3 repeat. Data was analyzed by Analysis of Variance (ANOVA) at 95% confidence level and continued with the test of Duncan Multiple Range Test (DMRT). The result showed that the interaction between media weight and number of seeds had significant effect on wet weight of plant. but media weight factor treatment had significant effect on plant height, wet weight of plant, tuber number and tuber weight . The optimal result is weight media 10 kg with 2 seeds number. The weight treatment of 10kg media with the number seeds of 2 resulted in the maximum growth and production.. Keywords: Potatoes, polybag, media weight, seeds number.